An EU–GDPR Based Privacy Assurance Framework for Data Processors in Software Package Implementation Industry in India - Rajagopalan, Premnath (Digital Repository of Theses, 2026)
In the ever-changing landscape of data protection and privacy regulations, exemplified by the EU General Data Protection Regulation (EU-GDPR, Regulation (EU) 2016/679), Indian data processors within the software package implementation sector face significant compliance challenges. This study aims to report these challenges by emerging a tailored privacy assurance framework, finely tuned to the unique context of package implementation in India. This research reveals the gaps or limitations in the Digital Personal Data Protection (DPDP) Act in India as a second best solution for software package implementation sector but also proposes a new framework with standards as a first best solution in order to be in full compliance with the market expectation from the globalized clients, mainly from EU regarding the data protection and privacy regulations in the globalized economy which is subject to constant technological changes. In a globalized economy subject to constant technological changes, meeting these regulatory expectations becomes imperative. India's software package implementation sector plays a pivotal role globally, contributing nearly 8% to the nation's GDP during 2017-2018, has grown to account for 11% during 2021-2023. Making it a formidable player in global IT arena. The sector's dominance, holding 55% of the global IT outsourcing share, underscores the essential for a strong data protection framework, with the EU-GDPR emerging as a potential benchmark. The substantial contribution of the IT sector to India's GDP emphasizes the paramount need for a strong data protection framework. However, the emergence of stringent rules like the EU-GDPR and the DPDP Act has brought data security and privacy issues into sharp focus for Indian software package companies, functioning as data processors. Indian data processors now grapple with the intricate task of aligning their local corporate practices with the EU-GDPR and DPDP Act requirements while serving European clients. This research adopts a multifaceted approach, incorporating a comprehensive literature review, surveys targeting Indian software package organizations, and in-depth interviews with key department stakeholders. The survey encompasses various departments within these organizations, including Legal, HR, administration, and IT. Additionally, the plan is to include overall data on the percentage of GDP contributed by the surveyed companies which make it crucial impact on the need for data privacy for these organizations. This research anticipates yielding valuable understandings into the current state of GDPR and DPDP Act compliance amongst Indian companies functioning as data processors. The focus is on identifying areas of merging and separation between EU-GDPR and DPDP Act standards and prevalent Indian privacy practices. Furthermore, this research aims to present a meticulously tailored privacy assurance framework designed to bridge these gaps and facilitate compliance with the EU-GDPR and DPDP Act, particularly for data processors in the Indian software package execution sector. The findings will be discussed in the background of privacy and data protection in India's software package implementation industry. The proposed framework will undergo detailed evaluation to determine its feasibility and effectiveness in addressing compliance disparities and challenges. The study will also cover on the potential challenges and advantages associated with implementing such a Privacy Framework. This research presents a comprehensive strategy for addressing the intricate challenges related to data privacy and protection compliance encountered by software package implementers in India. By crafting a privacy assurance framework tailored to the Indian context, this research aims to identify the necessary data security measures within the scope of the EU-GDPR considering also DPDP Act. These measures can be adopted by Indian companies to achieve compliance with EU standards, ultimately enhancing the sector's competitive edge, fostering quality standards in data protection, and ensuring business continuity and profit generation. Keywords: EU-GDPR, Data Protection, Data Processors, Privacy Assurance Framework, Software Package Implementation in India, DPDP Act, Data Security, Compliance, Client Data Protection.